Status epilepticus: the score question - Misirocchi, Francesco; De Stefano, Pia (Frontiers in Neurology, 2025)
Status epilepticus (SE) is a heterogeneous neurological emergency associated with high morbidity and mortality. Multiple prognostic scores have been developed, most of which primarily focus on short-term mortality. The Status Epilepticus Severity Score (STESS) and the Epidemiology-Based Mortality Score in SE (EMSE) remain the most extensively validated tools, while more recent models have addressed specific subgroups, functional outcomes, long-term survival, epilepsy development, and recurrence risk. Despite these advances, the predictive performance of current scores remains limited, largely due to reliance on post-hoc or subjective variables, lack of universally applicable cut-offs, and limited external validity. Moreover, their integration into clinical algorithms is minimal, confining their use mainly to retrospective risk adjustment in research context. Emerging approaches based on artificial intelligence offer improved predictive performance, but their clinical applicability is hampered by several issues. Future SE models should balance feasibility with accuracy, integrate variables across different stages of SE care, and align with standardized SE definitions and management, to become clinically valuable tools able to guide individualized SE management.